Mendelian randomization analysis revealed potential causal factors for systemic lupus erythematosus. Issue 3 (21st November 2019) - Mo, Xingbo; Guo, Yufan; Qian, Qiyu; Fu, Mengzhen; Lei, Shufeng; Zhang, Yonghong; Zhang, Huan
Summary: Genome‐wide association studies (GWAS) have identified many loci for systemic lupus erythematosus (SLE). However, identification of functionally relevant genes remains a challenge. The aim of this study was to highlight potential causal genes for SLE in the GWAS loci. By applying Mendelian randomization (MR) methods, such as summary data‐based MR (SMR), generalized SMR and MR pleiotropy residual sum and outlier, we identified DNA methylations in 15 loci and mRNA expression of 21 genes that were causally associated with SLE. The identified genes enriched in 14 specific KEGG pathways (e.g. SLE, viral carcinogenesis) and two GO terms (interferon‐ γ ‐mediated signaling pathway and innate immune response). Among the identified genes, UBE2L3 and BLK variants were significantly associated with UBE2L3 and BLK methylations and gene expressions, respectively. UBE2L3 was up‐regulated in SLE patients in several types of immune cells. Methylations (e.g. cg06850285) and mRNA expression of UBE2L3 were causally associated with SLE. Methylation site cg09528494 and mRNA expression of BLK were causally associated with SLE. BLK single nucleotide polymorphisms that were significantly associated with SLE were strongly associated with plasma cathepsin B level. Deep analysis identified that plasma cathepsin B level was causally associated with SLE. In summary, this study identified hundreds of DNA methylations and genes as potential risk factors for SLE. Genetic variants in UBE2L3 gene might affect SLE by influencing gene expression. Genetic variants in BLK gene might affect SLE by influencing BLK gene expression and plasma cathepsin B protein level. Abstract : Expressions of 21 genes and 152 methylations were causally associated with systemic lupus erythematosus (SLE). UBE2L3 and BLK variants were significantly associated with UBE2L3 and BLK methylations and gene expressions, respectively. Plasma cathepsin B level may be causally associated with SLE.